1996
DOI: 10.2307/30141296
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Respirator Training on the Ability of Healthcare Workers to Pass a Qualitative Fit Test

Abstract: Our study indicates that training in the proper use of respirators is important, but the method of training may not be, as the two methods we evaluated were nearly equivalent in their pass rates on fit testing (94% versus 91%). Fit testing as part of training may have enhanced the performance of our participants marginally, but was more time consuming and accounted for most of the excess cost.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(4 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…As a result of the lack of availability of standard N95 FFRs, the iMASC system was not compared with standard-of-care N95 FFRs. Previous studies have demonstrated that a respirator user gains experience with subsequent donnings and may result in improved fit-test pass rate biasing our results [11][12][13] ; thus, it will important to assess fit testing in inexperienced subjects. While Bitrex is the preferred choice for fit test solution as a leak detection, 14 saccharin was chosen due to availability and use in OSHA-approved qualitative fit tests.…”
Section: Discussionmentioning
confidence: 95%
“…As a result of the lack of availability of standard N95 FFRs, the iMASC system was not compared with standard-of-care N95 FFRs. Previous studies have demonstrated that a respirator user gains experience with subsequent donnings and may result in improved fit-test pass rate biasing our results [11][12][13] ; thus, it will important to assess fit testing in inexperienced subjects. While Bitrex is the preferred choice for fit test solution as a leak detection, 14 saccharin was chosen due to availability and use in OSHA-approved qualitative fit tests.…”
Section: Discussionmentioning
confidence: 95%
“…The use of reality-based education methods, such as clinical simulation, has been shown to help significantly reduce the contamination associated with PPEs' management [13]. However, while some authors have reported fewer errors using methodologies with active versus passive formations [34], others have not found significant differences in compliance with the protocol [35,36], or even the opposite, finding significant differences in favor of the use of online methodologies (e.g., mobile video) instead of conventional learning strategies in health professionals managing PPEs [31], which may be due to the immediacy (any moment, any time) offered by these modern approaches in a profession marked by constantly changing schedules and routines determined by patient conditions. It is true that both modalities have common features, which can be, among others, the possibility of downloading the content and assignments, as if students were taking notes in a face-to-face lesson, or the possibility of starting a debate or reflection process during lessons remotely thanks to videoconference platforms.…”
Section: Discussionmentioning
confidence: 99%
“…18 Clayton and Vaughn stated that fit-testing plays an important role in reinforcing training as users forget how to correctly don and use their respirators while Hannum et al concluded that fit-testing as part of training marginally enhanced the ability of healthcare workers to wear respirators properly and pass a fit-test. 26,27 Doffing safely and in the proper sequence is also important to prevent self-contamination. 28 According to section 8.8 of CSA Standard Z94.4-02, refresher training for respirator users is to be provided at least every two years.…”
Section: Respirator User Education and Training: Frequency And Knowle...mentioning
confidence: 99%